Pengaruh Servant Leadership Dan Empowerment Terhadap Organizational Citizenship Behavior Melalui Kepuasan Kerja Pada PT. Bank Sumut - Ulfah Mach Fira; Ani Muwarni Muhar; Sarah Imelda (Cattleya Darmaya Fortuna, 2023)
This study aims to determine the effect of servant leadership and empowerment on job satisfaction partially. To determine the effect of servant leadership, empowerment and job satisfaction on organizational citizenship behavior. To find out whether job satisfaction mediates the influence of servant leadership and empowerment on organizational citizenship behavior at PT. SUMUT Bank. The total population in this study amounted to 130 people, and by using a saturated sampling technique, a sample of 130 people was obtained. The analysis technique used is path analysis. The results showed that servant leadership had no effect on job satisfaction, empowerment had a positive and significant effect on job satisfaction. Servant leadership has no effect on organizational citizenship behavior. Empowerment has a significant effect on organizational citizenship behavior. Job satisfaction has a significant effect on organizational citizenship behavior at PT. SUMUT Bank. Job satisfaction does not mediate the influence of servant leadership on organizational citizenship behavior. Job satisfaction does not mediate the effect of empowerment on organizational citizenship behavior at PT. SUMUT Bank.